Reinterpreting the Mineral Collections in Rome's Museum of Civilizations - Silvia Pireddu (Museum & Society)
Natural history museums often emphasize technical expertise, which can lead to the isolation of their collections from broader political, cultural, and social contexts. This trend is similarly observed in the presentation of mineral collections, where cultural, historical, and ethical dimensions are frequently overlooked. However, museums with mineral displays have the potential to adopt engagement strategies that foreground the anthropological aspects of these collections. A noteworthy example of this integrative approach is found at the Museum of Civilizations in Rome. This museum hosts ISPRA’s (Istituto Superiore per la Protezione e la Ricerca Ambientale – Italian Institute for Environmental Protection and Research) geological and historical collections, former collections from the Museum of Italian Africa, and contemporary artworks. The institution merges these aesthetic, scientific, and anthropological collections to advance a decolonized narrative. It also incorporates art installations that enhance the understanding of cultural and political issues facing anthropology and science museums today. This article uses the museum’s innovative approach as a case study to explore the intersection of scientific and historical discourses.